Determinants of Venezuela's Equilibrium Real Exchange Rate - Zalduendo, Juan. (Washington, D.C. : International Monetary Fund, 2006)
The Venezuelan Bolivar is pegged to the U.S. dollar and supported by foreign exchange restrictions. To assess the appropriateness of the peg during the current period of high oil export earnings and the likely consequences of a liberalization, this paper attempts to disentangle the effects of oil prices from other factors underlying the equilibrium real exchange rate, and examines the role of foreign exchange controls by extending the application of a vector error correction (VEC) model to parallel market exchange rates. Several findings are worth noting. First, oil prices have indeed played a significant role in determining a time-varying equilibrium real exchange rate path. Second, oil prices are not the only important determinant of the real effective exchange rate: declining productivity is also a key factor. Third, appreciation pressures are rising. Finally, the speed of convergence of a VEC model using parallel rather than official rates is higher, suggesting that the government has been able to maintain sharp deviations between the official and equilibrium rates because of Venezuela's oil dependency and the concentration of oil income in government hands.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet